2020
DOI: 10.3390/ijms21041288
|View full text |Cite
|
Sign up to set email alerts
|

Cbx2, a PcG Family Gene, Plays a Regulatory Role in Medaka Gonadal Development

Abstract: Chromobox homolog 2 (CBX2), a key member of the polycomb group (PcG) family, is essential for gonadal development in mammals. A functional deficiency or genetic mutation in cbx2 can lead to sex reversal in mice and humans. However, little is known about the function of cbx2 in gonadal development in fish. In this study, the cbx2 gene was identified in medaka, which is a model species for the study of gonadal development in fish. Transcription of cbx2 was abundant in the gonads, with testicular levels relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…According to a previous study, CBX2 is a key member of the polycomb group (PcG) family and CBX2 mRNA was predominately localized in spermatogonia and spermatocytes, as demonstrated by in situ hybridization (ISH) (25). Tatavosian et al found that CBX2 undergoes phase separation to form condensates and that these CBX2 condensates concentrate DNA and nucleosomes (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous study, CBX2 is a key member of the polycomb group (PcG) family and CBX2 mRNA was predominately localized in spermatogonia and spermatocytes, as demonstrated by in situ hybridization (ISH) (25). Tatavosian et al found that CBX2 undergoes phase separation to form condensates and that these CBX2 condensates concentrate DNA and nucleosomes (26).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, CBX2 is a key member of the polycomb group (PcG) family and CBX2 mRNA was predominately localized in spermatogonia and spermatocytes, as demonstrated by in situ hybridization (ISH) ( 25 ). Tatavosian et al.…”
Section: Discussionmentioning
confidence: 99%
“…In various vertebrates, dozens of effector pathways and genes involved in sex determination and gonadal development have been identified, including pathways involved in the Sox [ 33 ], Dmrt [ 34 ], Hox [ 35 ], and Wnt [ 36 ] gene families, as well as genes such as Sox9, Sox3, DAX1, AMH, Dmrt1, and Fgf9. The current research has demonstrated that gonadogenesis and development in fish are also co-regulated by these genes [ 37 , 38 ]. We performed a functional analysis of the DEGs, based on the known sequences in the database, and discovered that the DEGs were significantly enriched in the “reproductive process”, “ RNA modification”, “amide biosynthetic process”, “lipid metabolic process”, and “peptide transport processes”.…”
Section: Discussionmentioning
confidence: 99%
“…The CBX2 gene belongs to the Polycomb group (PcG) of protein family, which is involved in various biological processes, such as cell cycle regulation, cell differentiation, cell senescence, and X chromosome inactivation ( Mao et al, 2019 ; Plys et al, 2019 ). Previous research has indicated that CBX2 was an epigenetically modified transcription repressor ( Chao et al, 2020 ). Recent studies have linked high CBX2 expression with the poor prognosis of HCC patients.…”
Section: Discussionmentioning
confidence: 99%